2021
DOI: 10.1111/pcmr.13007
|View full text |Cite
|
Sign up to set email alerts
|

The AMP‐dependent kinase pathway is upregulated in BAP1 mutant uveal melanoma

Abstract: UM represents approximately 5% of melanoma cases (Kaliki & Shields, 2017). Despite the low incidence of UM, which is diagnosed in ~2,000 adults annually in the United States, about 50% of patients develop metastasis that arises primarily in the liver (Diener-West et al., 2005). Following diagnosis of metastatic UM, disease prognosis is usually poor and median survival is 6-12 months (Krantz et al., 2017). The poor outcomes are largely due to ineffective responses of metastatic UM to targeted therapies such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Moreover, we found that AMPK knockdown by siRNA reduced uveal melanoma cell growth (Appendix Fig S5). This is reminiscent of a previous study showing similar effect of AMPK inhibition in uveal melanoma cells (Chua et al , 2022) and suggesting that AMPK inhibition does not promote uveal cell proliferation.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, we found that AMPK knockdown by siRNA reduced uveal melanoma cell growth (Appendix Fig S5). This is reminiscent of a previous study showing similar effect of AMPK inhibition in uveal melanoma cells (Chua et al , 2022) and suggesting that AMPK inhibition does not promote uveal cell proliferation.…”
Section: Discussionsupporting
confidence: 83%
“…Biallelic inactivation of the tumor-suppressor BAP1 is the distinctive genomic feature of class 2 UM, which occurs through the mutation of one allele and the whole-chromosome loss of the other allele [ 4 ]. While we and others have extensively investigated the downstream effects of BAP1 loss in UM cells [ 5 , 6 , 7 ], the mechanism by which BAP1 loss leads to metastasis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…127,128 Loss of functional BAP1 is associated with tumorigenesis or BAP1 cancer syndrome, which involves uveal melanoma, mesothelioma, renal cell carcinoma (RCC), HCC, cutaneous melanoma, and breast cancer. [129][130][131] Further, the BAP1 expression has been lower in human lung adenocarcinoma samples than in normal samples and is positively correlated with patient survival. Observations in an animal model of lung adenocarcinoma demonstrated the reduction of BAP1 level during tumor growth that was associated with the reduction of KELCH-ECH-associated protein 1 (Keap-1) expression and increased nuclear factor E2-related factor-2 (Nrf-2, a redox-sensitive transcription factor) activity as well as suppression of oxidative stress.…”
Section: Deubiquitinasesmentioning
confidence: 96%
“…It also affects cell cycle proteins, mitochondrial function, cell survival, tumor metabolism, and immune responses 127,128 . Loss of functional BAP1 is associated with tumorigenesis or BAP1 cancer syndrome, which involves uveal melanoma, mesothelioma, renal cell carcinoma (RCC), HCC, cutaneous melanoma, and breast cancer 129–131 . Further, the BAP1 expression has been lower in human lung adenocarcinoma samples than in normal samples and is positively correlated with patient survival.…”
Section: The Role Of Ups Dysregulation In Tumorigenesismentioning
confidence: 99%